KUALITAS PRODUK BEDAK TWO-WAY CAKE DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) DAN FMEA PADA PT UNIVERSAL SCIENCE COSMETIC - Susanto, Edi (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
With a good product quality, it is expected that the consumers can trust the product.Â Fulfilling this need, a quality improvement program is implemented with the aim of producingÂ products with higher quality but with less cost. The problem faced by PT USC is the number ofÂ defects in production caused by the lack of quality control to product defects. The method used toÂ solve the problem is FMEA and seven tools methods consisting of control charts, pareto diagram,Â and cause-effect diagram. By performing calculations sigma capability, sigma value 4.7064Â obtained by following the reference Motorolaâs sigma. For new company who early founded, to sayÂ the sigma value is pretty good although it should be continuously improved to nearly the level ofÂ six sigma.